(untitled) (Al-Qamar, 2025)
This study aims to highlight translation errors that occur due to the way translators understand Quranic words. Some translators interpret these words automatically through a stereotypical lens, while others rely on the exegesis of the Quran to explain them. With this in mind, our research focuses on identifying the potential errors that arise when translators overlook polysemous words, which may lead to misleading translations. Based on this, our research examines how stereotypical errors impact the quality of translations of certain Quranic terms. The key finding of the study reveals that one of the main reasons translators commit stereotypical errors is their failure to rely on the linguistic interpretations of Quranic words. This, in turn, results in an English version of the Quran that significantly deviates from the original.